The Role of Assent in Article 2 and Article 9 - Michael M. Greenfield (Washington University Law Quarterly, 1997)
After briefly reviewing the history of consumer protection in the UCC and its revisions, this Article analyzes the approaches of proposed revisions to Articles 2 and 9 with a focus on the assent necessary for apparent agreement to become binding on consumers in sales and secured transactions.
Keywords: Consumer protection; Offer & acceptance (Contracts); Sales contracts; Collateral security